Effects of high-dose selenium-enriched yeast on laying performance, egg quality, clinical blood parameters, organ development, and selenium deposition in laying hens. (1st February 2019) - Lu, J; Qu, L; Shen, M M; Wang, X G; Guo, J; Hu, Y P; Dou, T C; Wang, K H
ABSTRACT: Organic selenium (Se ) supplementation from Se-enriched yeast (SY ) has been advocated and approved for use in animal feeds by some nutritionists and researchers rather than inorganic Se from sodium selenite. However, there is little available safety data of SY in laying hens. A subchronic study was conducted to determine if high-dose SY affects the safety of hens. A total of 768, 30-wk-old, Hy-Line Brown hens were randomly assigned to 1 of 4 groups (192 laying hens per group) with 6 replicates of 32 birds each. After a 2-wk acclimation period, the birds were fed diets supplemented with 0, 0.3, 1.5, or 3.0 mg/kg Se from SY for 12 wk. Throughout the study period, clinical observations and laying performance were measured. The hematological and chemical parameters of blood samples and the Se concentration in eggs were examined after SY supplementation for 4, 8, and 12 wk, and the egg quality was measured after 12 wk. At the end of the study, full post-mortem examinations were conducted: breast Se concentrations were measured, visceral, and reproductive organs were weighed, and specified tissues were collected for subsequent histological examinations. Although the Se concentrations in the eggs and breast meat from hens fed 3.0 mg/kg of Se from SY were 1036.73% and 2127.93% higher ( P < 0.001) than those from hens fed a basal diet after 12 wk, no treatment-related changes of toxicological significance were observed. Therefore, up to 3 mg/kg organic Se from SY can be used to supplement the diets for laying hens without adverse effects following 84-d administration.